Counter Narrative Sexual Violence in Alternative Media Mubadalah.id - Ratu Arti Wulan Sari; Ahmad Jamaludin (IAIN Batusangkar, 2022)
The media has a strategic role in providing an understanding and description of something through the narratives it creates, including the narrative about sexual violence. The issue of sexual violence has become a sensitive issue so the media should not only provide information to catch up with the number of readers, but the media in the narrative must take sides with victims of sexual violence as a form of protection. The purpose of this study is to find out how the narrative of sexual violence is packaged by the alternative media Mubdalam. id. This research is qualitative research using Sara Mills's discourse analysis method and using Antonio Gramsci's theory of hegemony. The results of the study show that the narratives presented by the alternative media Mubadalah.id are (1) the subject of the narrator as a person who advocates using the victim's perspective and the perspective of positive law and Islamic religious rules. (2) The alternative media, Mubadalah.id, leads the readers to take sides with the victims and ignites the readers to be able to do advocacy together against sexual violence. In conclusion, the alternative media Mubadalah.id is a media that has a counter-narrative and counter-hegemony on the issue of sexual violence that is developing in the community.